2022
DOI: 10.1177/15589447211073830
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Severity and the Risks of Postoperative Complications and Extended Length of Stay Following Primary Total Elbow Arthroplasty

Abstract: Background: Anemia is a modifiable risk factor that may influence postoperative complications following orthopedic surgical procedures. The objective was to determine the influence of preoperative anemia severity on postoperative complications and length of stay (LOS) following total elbow arthroplasty (TEA). Methods: The American College of Surgeons National Surgical Quality Improvement Program registry was queried from 2006 to 2019 for patients undergoing primary TEA. Using the World Health Organization defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A study of 589 total elbow arthroplasty patients, using the ACS-NSQIP database, discovered that anemia was a significant predictor of prolonged LOS, with the proportion of patients with prolonged LOS increasing significantly with increasing levels of anemia. [ 39 ] In another case-control study involving 1259 patients with hip fractures, [ 40 ] Cao H et al reported that Hb was a significant predictor of prolonged LOS (OR = 1.920, 95% CI: 1.045 to 3.529, P = .036). However, in an earlier study of 317 elderly hip fracture patients, no correlation between Hb and LOS was found after adjusting for age and gender ( P = .130).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 589 total elbow arthroplasty patients, using the ACS-NSQIP database, discovered that anemia was a significant predictor of prolonged LOS, with the proportion of patients with prolonged LOS increasing significantly with increasing levels of anemia. [ 39 ] In another case-control study involving 1259 patients with hip fractures, [ 40 ] Cao H et al reported that Hb was a significant predictor of prolonged LOS (OR = 1.920, 95% CI: 1.045 to 3.529, P = .036). However, in an earlier study of 317 elderly hip fracture patients, no correlation between Hb and LOS was found after adjusting for age and gender ( P = .130).…”
Section: Discussionmentioning
confidence: 99%